About work of anti-bribery Commission under Omsk Provincial Council of national economy in early 1920’s - T. V. Glazunova; V. V. Germizeeva (Омский научный вестник: Серия "Общество. История. Современность")
The article is devoted to the work of the commission established in early 1920s in Omsk to combat economic crimes and mismanagement. Also, the commission engaged in «cleaning» personnel on the basis of their reliability. The study allows deeper study of the mechanisms of implementation of this campaign on specific examples. The authors studied the legislative framework of the early 1920s, summed up the activities of the commission, and used and analyzed previously unpublished archival sources on the work of the commission identified in the historical archive of the Omsk region